(untitled) (Teacher’s World: Journal of Education and Research, 2024)
This study examines the undocumented narratives around the persistent desire for education among transgender individuals in Bangladesh, highlighting the challenges they have encountered in their academic pursuits. Through an analysis of the stories provided by eight adult transgender participants, this research identifies noteworthy factors that have led to the disparity observed in the educational aspirations of transgender individuals. In conjunction with in-depth interviews and interpretive phenomenological analysis, a narrative inquiry approach was utilized to acquire a comprehensive comprehension of the participants’ viewpoints regarding educational aspirations. The results of the study indicate several significant factors that contribute to the diminished educational aspirations of transgender students. The results of the study indicate several significant factors that contribute to the diminished educational aspirations of transgender students, such as falsified sex identity, social stigmas, bullying, abuse and harassment, teachers’ ignorance and unhelpful behavior, economic hardship and poverty, and unfavorable learning environments. The findings have highlighted the need for more open and accepting environments for transgender children and young adults, particularly in family and educational settings. Teacher’s World: Journal of Education and Res arch, 50(1): 7-20